Prevalence of Sero-Molecular Markers of Hepatitis C and B Viruses among Patients with β-Thalassemia Major in Northern West Bank, Palestine - Kamal Dumaidi; Amer Al-Jawabreh; Fekri Samarah; Maha Rabayaa (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. HCV and HBV present a great challenge in the management of β-thalassemia patients. Objective. The present study aimed to determine the prevalence of both HBV and HCV in multitransfused-dependent β-thalassemia patients in northern West Bank, Palestine, using sero-molecular markers. Methods. Serum sample from 139 multitransfused β-thalassemia patients were tested for HBV and HCV markers including HBsAg, anti-HBc, anti-HBs, HBV-DNA, and anti-HCV and HCV-RNA. Demographic data and selected clinical parameters were collected by means of a questionnaire and from the patients’ medical files. Results and Conclusion. The mean (±SD) age of patients was 18.1 years (±10.6). The overall prevalence of the HCV was 10% (14/139), which is 50 times higher than the normal Palestinian population (0.2%). Of which, 3 were positive for anti-HCV alone, 7 positives for HCV-RNA alone, and 4 positives for both anti-HCV and PCR-RNA. On the other hand, low prevalence of HBV was detected at a level of 0.7% (1/139). Only one patient had HCV-HBV coinfection. Twenty-five patients (19%) were positive for anti-HBc, while 99 (71%) were immune with the anti-HBs level above 10 IU/mL. Anti-HBc was insignificantly high (P=0.07) in HCV-positive cases. In conclusion, the prevalence of HCV among β-thalassemia patients is considered high compared to normal population. Determination of HCV prevalence should be based on the detection of both HCV-RNA and anti-HCV. On the contrary, HBV showed a low prevalence. A follow-up schedule and administration of booster dose of HBV vaccine is strongly recommended for β-thalassemia patients whose anti-HBs level <10 IU/ml.